Perbandingan Penerapan E-Government Negara Indonesia Dan Jepang - Sabrina, Dea Rahma; Dompak, Timbul; Khairina, Etika (Prosiding, 2024)
This study intends to investigate the similarities and differences between the implementation of e-Government in Indonesia and Japan, with the goal of identifying the most significant differences in approaches, progress, and challenges that both countries are currently facing. It is a qualitative research method that is used, and the data collection process is carried out through the study of literature from a number of journals and articles that are related to the topic. E-Government systems have been actively developed by countries such as Indonesia and Japan in response to globalization and advancements in information technology. The goal of these systems is to improve the efficiency, accessibility, and transparency of governance. Electronic government is one of the technological advancements that the government has adopted in order to facilitate services and as a tool for delivering information to the public through the internet or social media that is, of course, related to issues that are being addressed by the government. The information and communication technology (ICT) infrastructure in Japan is extremely advanced, with a high percentage of people using smartphones and extensive internet connectivity. In the meantime, Indonesia continues to struggle with increasing internet accessibility and the penetration of information and communication technology in rural areas.